A Visual Approach For Requirement Traceability - Madaki, Abdulkadir Ahmad (2022)
Requirement traceability is a significant method of tracing and identifying the life of requirement in forward and backward directions during software development lifecycle. It is used to support impact analysis, requirement change, maintenance, verification, and validation of a software system. Visualization is one of the most suitable visual representations of requirement traceability data as it has so many aspects that can be explored. It offers detail and visible demographic symbols to show the traceability of requirements artefacts relationships. However, displaying many traceability links effectively and efficiently is a big challenge, because a software system with large numbers of artefacts and traceability links quickly gives rise to scalability and visual clutter issues. Therefore, a visual framework is designed and implemented as a tool to visualize and manage the traceability of requirements artefacts relationships. The framework follows an advance graphical user interface guide for Visual Information-Seeking which focus on overview first, zoom and filter, then details-on-demand. The tool used visualization techniques as colour-coded symbols on a node-link diagram to present data. Users can traverse the graph for an impact analysis method to understand data and make decisions during the software development life cycle. The evaluation results show a positive respond in terms of usefulness and ease of use factors. The average score mean for usefulness are 4.33 (86%), whereas the average score mean for ease of use are 4.25 (85%). This results show that the framework is useful in tracing links between requirements artefacts, easy to use as is highly effective to improve user interaction.